2021
DOI: 10.1002/jmor.21330
|View full text |Cite
|
Sign up to set email alerts
|

Does the bowfin gas bladder represent an intermediate stage during the lung‐to‐gas bladder evolutionary transition?

Abstract: Whether phenotypic evolution occurs gradually through time has prompted the search for intermediate forms between the ancestral and derived states of morphological features, especially when there appears to be a discontinuous origin. The gas bladder, a derived character of the Actinopteri, is a modification of lungs, which characterize the common ancestor of bony vertebrates. While gas bladders and lungs are similar in many ways, the key morphological difference between these organs is the direction of budding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To explore the regulation of the size and position of organs by the surrounding environments in vertebrates, the swim bladder, which some argue should rather be called the gas bladder in terms of function (Facey et al, 2022), may provide a good model. The swim bladder is a gas-filled sac located in the dorsal portion of the body that teleost fish uniquely acquired from the primitive lung (Facey et al, 2022;Funk et al, 2021;Funk et al, 2020). The primary role of the swim bladder in most teleost fishes is controlling buoyancy to maintain the vertical position in aquatic conditions, although it has specialized other roles in respiration, sound production, and sound reception in some species (Burton and Burton, 2018;Cook et al, 2024;Facey et al, 2022;Popper and Fay, 1993;Seymour et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To explore the regulation of the size and position of organs by the surrounding environments in vertebrates, the swim bladder, which some argue should rather be called the gas bladder in terms of function (Facey et al, 2022), may provide a good model. The swim bladder is a gas-filled sac located in the dorsal portion of the body that teleost fish uniquely acquired from the primitive lung (Facey et al, 2022;Funk et al, 2021;Funk et al, 2020). The primary role of the swim bladder in most teleost fishes is controlling buoyancy to maintain the vertical position in aquatic conditions, although it has specialized other roles in respiration, sound production, and sound reception in some species (Burton and Burton, 2018;Cook et al, 2024;Facey et al, 2022;Popper and Fay, 1993;Seymour et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the decade we have been visiting Oneida Lake, New York to search for nests of bowfins, now considered A. ocellicauda (Wright et al, 2022), to collect eggs for evolutionary developmental work (Cass et al, 2013;Funk et al, 2020aFunk et al, , 2020bFunk et al, , 2021, we have never observed spawning and we have rarely seen a female closely associated with a nest. Even so, the accessibility of males guarding eggs and fry on nests constructed in shallow water provided an opportunity to investigate mating in Amia with genetic data.…”
mentioning
confidence: 99%